IDENTIFIKASI ZONA LEMAH DI JALAN POROS SAMARINDA BONTANG DENGAN MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI WENNER SCHLUMBERGER - R, Achmad Fatoni; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2021)
ABSTRACT Some road bodies in East Borneo experienced landslide and land-deformation that presumably caused by weak zones. Aim of this research is to investigate weak zones existence by means of geoelectricity method. This research utilizes secondary data of geoelectricity method Wenner-Schlumberger configuration. Weak zones existence caused landslide and land-deformation interpreted with Res2DinV modeling software. Result of this research showed weak zones located in all acquisition lines; in line 1 existed in 13 – 26 meters depth; in line 2 existed in 16 – 36 meters depth; in line 3 existed in 13 – 40 meters depth; and in line 4 existed in 10 – 28 meters depth. Commonly, rock composition of a weak zones is claystone with 20 – 30 Ωm resistivity value and sandy-claystone with 30 – 250 Ωm resistivity value. Key Words: Weak Zones, Land deformation, Resistivity, Wenner-Schlumberger.